2003
DOI: 10.1002/humu.10228
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced allele-specific PCR discrimination in SNP genotyping using 3? locked nucleic acid (LNA) primers

Abstract: The specificity and reliability of locked nucleic acid (LNA) substitution at the 3' position of allele-specific PCR (AS-PCR) primers for SNP detection was investigated in direct comparison to DNA primers. Both plasmid and human genomic DNA templates were examined in this study. All possible DNA and 3' LNA mismatch combinations were tested in triplicate with the plasmid target. LNA primers yield consistently low amounts of mismatch products with all base combinations, whereas certain mismatches with DNA primers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(153 citation statements)
references
References 25 publications
(21 reference statements)
2
147
0
4
Order By: Relevance
“…Notably, we also evaluated primers with a locked nucleic acid modified 3 0 base to improve discrimination (27,28). Although this greatly improved specificity for qualitative applications (i.e., genotyping), it reduced the dynamic performance of the assay with poor linearity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we also evaluated primers with a locked nucleic acid modified 3 0 base to improve discrimination (27,28). Although this greatly improved specificity for qualitative applications (i.e., genotyping), it reduced the dynamic performance of the assay with poor linearity (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Based on NMR studies of LNA/DNA duplexes, it has been concluded that the main factor contributing to the extraordinary high stability of LNA-containing duplexes is a local change of the phosphate backbone geometry that favours a much higher degree of base stacking. [6][7][8][9][10][11][12][13] Figure 1c shows these melting curves. The heterozygotes now yielded two separated peaks with a DTm of 7.51C (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] This last mentioned possibility is based on some recently published reports, which documented the high discriminative power of fluorogenic probes containing LNA to differentiate between matched and mismatched duplexes in several techniques, but not yet applied in FRET assays. [14][15][16] However, FRET assays have become a major technique in the field of polymorphism analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[42] So called multiplex reactions in which two allele variants are differentiated in a single reaction tube are realized by adding a specific 5' tail sequences to each allele specific primer. The signal generation is thereby directly linked to the allele specific primer in the PCR amplification.…”
Section: Genotyping Through the 5'-3'-exonuclease Activity Of Dna Polmentioning
confidence: 99%